DETECTION OF MECHANICAL FAULTS ON TRANSFORMER WINDING USING FREQUENCY RESPONSE ANALYSIS (FRA) - Rohini D. Jiwane (International Journal of Innovations in Engineering Research and Technology, 2021)
Frequency Response Analysis (FRA) is the only reliable technique often called as tool for determining mechanical faults in transformer winding. There are many techniques available for the electrical fault detection. But FRA is the only tool for detection of internal (electrical as well as mechanical) faults in Power Transformer. FRA relies on graphical analysis interpretation of its signature/fingerprint and it is specially used to detect mechanical faults on transformer winding. As transformer is very simple but vital and expensive equipment in Electrical power system, hence it is prime responsibility of utility to increase the usable service time as well as decrease transformer life-cycle cost.